Complete shaking force and shaking moment balancing of spatial multibody systems with open kinematic chains - Khang, Nguyen Van; Dien, Nguyen Phong; Son, Pham Van (Vietnam Journal of Mechanics, 2005)
This paper deals with a solution for the problem of full shaking force and shaking moment balancing of spatial multi body systems with open kinematic chains. Firstly, the general conditions for complete dynamic balancing of spatial multibody systems are formulated. These include formulae for complete elimination of the resultant inertia force and inertia couple caused by all moving bodies. In the following example, the equations of complete shaking force and shaking moment balancing of a nine-bar direct drive manipulator are given.